Assessing patient capacity to consent to treatment: an integrative review of instruments and tools. Issue 17 (8th May 2013) - Lamont, Scott; Jeon, Yun‐Hee; Chiarella, Mary
<x xml:space="preserve">Abstract</x> Aims and objectives To provide a narrative synthesis of research findings on instruments or tools designed to aid assessment of patient capacity to consent to treatment. Background Capacity assessment is of significant priority within health care as a finding of incapacity is a vehicle for the removal of many of an individual's fundamental rights. Despite there being many instruments and tools available to aid health professionals in the assessment of patient capacity, there are no standardised guidelines from professional bodies that inform the assessment of mental capacity. Design Integrative review. Method Primary studies of instruments or tools concerning assessment of patient capacity to consent to treatment, published in English in peer‐reviewed journals between January 2005–December 2010, were included in the review. Review papers of capacity assessment instruments were included for years including and prior to 2006. Results Nineteen instruments were found which assess patient capacity to consent. Key themes were identified in terms of capacity domains assessed, psychometric properties, instrument implementation, patient populations studied and instrument versus clinician judgement. Conclusion Despite a plethora of capacity assessment instruments and tools available, only a small number of instruments were found to have demonstrated both reliability and validity. Further research is required to improve the validity of existing capacity assessment instruments. Relevance to clinical practice Increased attention to patient rights and autonomy arguably places a considerable burden on healthcare professionals to facilitate capacity assessments across a continuum of health care. Despite a plethora of capacity assessment instruments and tools being available to healthcare professionals, a comprehensive assessment requires time and is often difficult in the acute care setting. A strictly formulaic approach to the assessment of capacity is unlikely to capture specific individual nuances; therefore, capacity assessment instruments should support, but not replace, experienced clinical judgement.